Permanent-magnet flux-switching integrated starter generator with different rotor configurations for cogging torque and torque ripple mitigations - Fei, Wei-Zhong; Luk, Patrick Chi-Kwong; Shen, Jian-Xin; Xia, Bin; Wang, Yu (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper investigates the cogging torque and torque ripple features of a permanent-magnet flux-switching integrated starter generator. The effects of the rotor pole arc width on the cogging torque, torque ripple, and output torque are first established using finite-element analysis (FEA). Three torque ripple reduction techniques based on the optimization of three different rotor pole configurations, namely, uniform, step skewed, and axial pairing, are then proposed. The torque characteristics of each rotor configuration at varying load currents and phase angles are studied in detail. A prototype machine with a common stator and the three optimized rotor configurations are built for experimental validation. Both the FEA results and the experimental tests show that the step skewed and axial pairing techniques can alleviate the cogging torque significantly, but the latter is less effective than the former in reducing the overall torque ripple.
Keywords: Axial pairing; back electromotive force (EMF); cogging torque; finite-element analysis (FEA); phase angle; reluctance torque; step skew; torque ripple